Wpływ wojny w Ukrainie na rozwój polityki bezpieczeństwa i obrony Unii Europejskiej (Politeja, 2024)
THE IMPACT OF RUSSIA’S 2022 INVASION OF UKRAINE ON EU SECURITY AND DEFENCE POLICYIn recent years, the European Union has continuously expanded its role in the area of security and defense policy. This process gained momentum following Russia’s full-scale invasion of Ukraine in February 2022. New decisions and initiatives on common defense were developed due to the effects of the war, which changed the dynamics of interaction between institutions and member states. The analysis highlights how the EU is using the opportunities created by crises to strategically expand its security policy mandate. It also examined how the war in Ukraine led to the establishment of new security and defense initiatives, which affected its geopolitical position.